2020
DOI: 10.3389/fpls.2019.01804
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Warming and N Deposition on the Physiological Performances of Leymus secalinus in Alpine Meadow of Qinghai-Tibetan Plateau

Abstract: Warming and Nitrogen (N) deposition are key global changes that may affect ecophysiological process of territorial plants. In this paper, we examined the effects of warming, N deposition, and their combination effect on the physiological performances of Leymus secalinus. Four treatments were established in an alpine meadow of Qinghai-Tibetan plateau: control (CK), warming (W), N deposition (N), and warming plus N deposition (NW). Warming significantly decreased the photosynthetic rate (A net), stomatal conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 72 publications
3
10
0
Order By: Relevance
“…2), indicating that F v / F m may not be a sensitive indicator for drought‐stressed C. mongolicum seedlings. Inconsistent with the findings of Shen et al (2020) and Wang & Chen (2019) that additional N improves chlorophyll content, we found that N inputs significantly decreased chlorophyll a and a + b in the assimilating shoots of C. mongolicum seedlings (Figure S1). This may be because the influences of N addition on chlorophyll are species‐specific (Zhang et al 2017), and the differences in structure and functions between foliage and assimilating shoots might explain these disparate phenomena.…”
Section: Discussionsupporting
confidence: 90%
“…2), indicating that F v / F m may not be a sensitive indicator for drought‐stressed C. mongolicum seedlings. Inconsistent with the findings of Shen et al (2020) and Wang & Chen (2019) that additional N improves chlorophyll content, we found that N inputs significantly decreased chlorophyll a and a + b in the assimilating shoots of C. mongolicum seedlings (Figure S1). This may be because the influences of N addition on chlorophyll are species‐specific (Zhang et al 2017), and the differences in structure and functions between foliage and assimilating shoots might explain these disparate phenomena.…”
Section: Discussionsupporting
confidence: 90%
“…Warming increase the temperature of air and soil, and reduce soil water content, finally leading to dramatic ecological effects on plants (Allison et al, 2018;Samaniego et al, 2018). Many studies found that warming-induced decrease in soil moisture might be the major reason of photosynthesis inhabitation (Reich et al, 2018;Shen et al, 2020). In our study, the decrease of soil moisture in OTCs did not cause soil drought (22.3%), so the presence of an OTC was not an additional source of drought stress (Pugnaire et al, 2020).…”
Section: Discussionmentioning
confidence: 46%
“…Interestingly, the P n of E. nutans decreased with increased temperature, while that of P. anserina increased. Shen et al (2020) also found that the P n of L. secalimus significantly decreased under warming, suggesting that warming can negatively limit plant photosynthesis. This is because the air temperature was high in the growing season (July), and thus the leaf temperature of E. nutans exceeded its optimal temperature, leading to a decrease in P n .…”
Section: Discussionmentioning
confidence: 87%
“…In the past years, a genome-wide association study (GWAS) was performed to identify QTLs for GER resistance using single-locus models (Han et al 2018 ). However, multi-locus models such as fixed and random model circulating probability unification (FarmCPU, Liu et al 2016 ) have been found to be more powerful in detecting SNP-trait associations with a lower rate of false positives and false negatives than single SNP-based models, especially for traits with complex genetic architecture (Abed and Belzile 2019 ; Kaler et al 2020 ; Malik et al 2019 ; Miao et al 2019 ; Odilbekov et al 2019 ; Wei et al 2017 ; Xu et al 2018 ; Zhang et al 2019 ; Zhu et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%